Method for producing hollow spherical alumina particles
Patent Information
- Application Number
- JP2025062609
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-04-04
AI Technical Summary
【0007】 本発明による中空球状アルミナ粒子は、特許文献1のアルミナ粒子と同様にαアルミナ由来であるが、平均粒径(D50)が1.0~3.5μmであり、かつD90が6μm以下であるものを提供する。得られたアルミナ粒子は、特許文献1と同様に、耐熱性、耐熱衝撃性、耐薬品性及び高温強度特性を持ち、中空かつ球状の特性が軽量性、断熱性、流動性等などに優れていて、樹脂、ゴム等への高機能配合材、電子材料関連の放熱用フィラー、電子部材の研磨用フィラー等への展開が期待される。特に、粒径の小さなアルミナ粒子で中空のものは、薄膜の樹脂シートの比誘電率を低下することに寄与することも考えられる。
Smart Images

Figure 2026168993000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for producing hollow spherical alumina particles. [Background technology]
[0002] Hollow alumina particles are produced by various methods. The present inventors proposed a method for producing hollow spherical alumina particles in Japanese Patent No. 7560195 (Patent Document 1). This patent describes a two-step method for producing spherical alumina particles that are hollow inside and have through-holes to the outside, comprising: a first step of drying and granulating an aqueous solution of basic aluminum lactate in air or an inert gas at a gas pressure of 0.01 to 1 MPa at a temperature of 210 to 280°C to form hollow dried granules in which the volatile content of the granules is controlled to 0 to 10% by mass and the bulk density to 0.2 to 0.7 g / cm3; and a second step of firing the dried granules obtained in the first step at a firing temperature in the temperature range of 1050°C to less than 1200°C for 2 to 8 hours to obtain hollow spherical alumina particles. The aluminum aqueous solution contains 0-0.01% by mass of iron (Fe), 0-0.01% by mass of calcium (Ca), 0-0.01% by mass of magnesium (Mg), and 0-0.01% by mass of silicon (Si), and also contains 0.005-1.2% by mass of alkali metal element ions, has a basicity of 60-80%, and contains 8-13% by mass of aluminum (in terms of Al2O3). The resulting hollow spherical alumina particles, in particle size distribution measurements, have a D50 of 5-50 μm and a D90 of 200 μm or less, are hollow inside, have through-pores to the outside, and have a specific surface area of 1-20 m². 2 We proposed a method characterized by having a value of / g and exhibiting an α-phase in its crystalline structure.
[0003] The hollow spherical alumina particles obtained in Patent Document 1 possess heat resistance, thermal shock resistance, chemical resistance, and high-temperature strength characteristics derived from α-alumina. Their hollow and spherical shape provides excellent lightness, heat insulation, and fluidity, making them suitable for applications such as high-performance compounding in resins and rubbers, heat dissipation fillers for electronic materials, and polishing fillers for electronic components. However, as mentioned above, the alumina particles obtained in Patent Document 1 have an average particle size (D50) of 5-50 μm and a D90 of 200 μm or less. There is a potential demand for alumina particles with even smaller particle sizes. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Patent No. 7560195 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] The present invention aims to provide hollow spherical alumina particles with a smaller particle size than the hollow spherical alumina particles obtained in Patent Document 1. [Means for solving the problem]
[0006] In other words, the present invention encompasses the following aspects: [1] A basic aluminum lactate aqueous solution was spray-dried and granulated in air or inert gas at a gas pressure of 0.4 to 1 MPa and an air flow rate of 200 to 4,000 L / min at a temperature of 180 to 280°C, with a liquid supply rate of 100 to 500 ml / min. Laser diffraction particle size distribution measurement of the dried granules showed that D50 was 1.0 to 4.5 μm, D90 was 8 μm or less, volatile matter was 0 to 10% by mass, and bulk density was 0.2 to 0.7 g / cm³. 3 A first step of forming a controlled hollow dry granule, The second step involves filling a calcination sheath with 50-80% of the volume of the sheath's internal volume using the dried granules obtained in the first step, A method for producing hollow spherical alumina particles, comprising: raising the temperature of the firing sheath obtained in the second step at 0.3 to 3°C / min, firing it at a firing temperature in the temperature range of 1,050°C to less than 1,200°C for 2 to 8 hours, and then lowering the temperature in the atmosphere at 0.3 to 10°C / min while introducing air at 50 to 200 ml / min, The basic aluminum lactate aqueous solution contains iron (Fe) in amounts of 0-0.01% by mass, calcium (Ca) in amounts of 0-0.01% by mass, magnesium (Mg) in amounts of 0-0.01% by mass, and silicon (Si) in amounts of 0-0.01% by mass, and also contains alkali metal element ions in amounts of 0.005-1.2% by mass, has a basicity of 60-80%, and contains aluminum in amounts of 8-13% by mass on an Al2O3 basis. The hollow spherical alumina particles, as measured by laser diffraction particle size distribution analysis, have a D50 of 1.0 to 3.5 μm and a D90 of 6 μm or less, are hollow inside and spherical, and have a specific surface area of 1 to 20 m². 2 A method for producing hollow spherical alumina particles, characterized by having a density of / g. [2] The hollow spherical alumina particles have a bulk density of 0.3 to 0.7 g / cm³. 3 A method for producing hollow spherical alumina particles as described in [1], characterized in that the crystalline phase of the hollow spherical alumina particles is the α phase. [3] The method for producing hollow spherical alumina particles according to [1] or [2], characterized in that the hollow spherical alumina particles exhibit a relative permittivity of 1.7 to 2.4 at a frequency f=1MHz measured by the capacitance method. [4] The method for producing hollow spherical alumina particles according to [1] or [2], characterized in that the aqueous solution of basic aluminum lactate is obtained by mixing an aluminum chloride solution with either or both sodium aluminate and potassium aluminate and water to form an aluminum hydroxide gel, washing the obtained gel with water, adding water to obtain an aluminum hydroxide slurry, and then adding lactic acid and reacting it. [Effects of the Invention]
[0007] The hollow spherical alumina particles according to the present invention are derived from α-alumina similarly to the alumina particles of Patent Document 1, and provide particles having an average particle diameter (D50) of 1.0 to 3.5 μm and a D90 of 6 μm or less. The obtained alumina particles have heat resistance, thermal shock resistance, chemical resistance and high-temperature strength characteristics similarly to Patent Document 1, and their hollow and spherical characteristics are excellent in light weight, heat insulation, flowability and the like, and are expected to be applied as high-performance compounding materials for resins, rubbers and the like, heat-dissipating fillers related to electronic materials, polishing fillers for electronic members, and the like. In particular, hollow alumina particles with small particle diameters are also considered to contribute to lowering the relative permittivity of thin-film resin sheets. Brief Description of the Drawings
[0008] [Figure 1] This is a graph of the particle size distribution of the hollow spherical alumina particles obtained in Example 1, which was measured by a dry method using a laser diffraction particle size analyzer (Mastersizer 3000 manufactured by Malvern Panalytical). The vertical axis of the graph represents the volume fraction (%), and the horizontal axis represents the particle size (μm). [Figure 2] This is a diagram showing the measurement results of the hollow spherical alumina particles obtained in Example 1, which were measured by the θ / 2θ method with a Cu target using an X-ray diffractometer (MiniFlex manufactured by Rigaku Corporation). [Figure 3] This is a diagram showing the measurement results of the alumina particles obtained in Comparative Example 6, which were measured by the θ / 2θ method with a Cu target using an X-ray diffractometer (MiniFlex manufactured by Rigaku Corporation). [Figure 4] This is a 50,000-times magnified SEM image of the alumina particles of Example 1, measured using a field emission scanning electron microscope (FE-SEM: JSM-7001F manufactured by JEOL Ltd.). [Figure 5] This is a 50,000-times magnified SEM image of the cross section of the alumina particles of Example 1, measured using a field emission scanning electron microscope (FE-SEM: JSM-7001F manufactured by JEOL Ltd.). Modes for Carrying Out the Invention
[0009] (Definition of Terms) In this specification, "hollow" means that there is a void inside the particle, and does not mean that there is a perfectly spherical space. Therefore, a void or space exists in part inside the alumina particle. Also, because the alumina particles are small, particle formation may be insufficient, so cage-like structures, such as those shown in Figure 5, may occur. In this specification, "spherical" does not mean a perfect sphere, but imperfect spheres, such as cage-like structures, are also described as "spherical."
[0010] (Content of the invention) In this invention, a basic aluminum lactate aqueous solution is spray-dried and granulated in air or an inert gas at a gas pressure of 0.4 to 1 MPa and an air flow rate of 200 to 4,000 L / min, at a temperature of 180 to 280°C, with a liquid supply rate of 100 to 500 ml / min. Laser diffraction particle size distribution measurement of the dried granules shows that D50 is 1.0 to 4.5 μm, D90 is 8 μm or less, volatile matter is 0 to 10% by mass, and bulk density is 0.2 to 0.7 g / cm³. 3 A first step of forming a controlled hollow dry granule, The second step involves filling a calcination sheath with the dried granules obtained in the first step to 50-80% of the volume inside the sheath, In the second step, the firing scabbard obtained is heated at a rate of 0.3 to 3°C / min, fired at a firing temperature within the range of 1,050°C to less than 1,200°C for 2 to 8 hours, and then cooled in the third step at a rate of 0.3 to 10°C / min while introducing air at a rate of 50 to 200 ml / min. In a method for producing hollow spherical alumina particles, The basic aluminum lactate aqueous solution contains iron (Fe) in amounts of 0-0.01% by mass, calcium (Ca) in amounts of 0-0.01% by mass, magnesium (Mg) in amounts of 0-0.01% by mass, and silicon (Si) in amounts of 0-0.01% by mass, and also contains alkali metal element ions in amounts of 0.005-1.2% by mass, has a basicity of 60-80%, and contains aluminum in amounts of 8-13% by mass on an Al2O3 basis. The hollow spherical alumina particles, as measured by laser diffraction particle size distribution analysis, have a D50 of 1.0 to 3.5 μm and a D90 of 6 μm or less, are hollow inside and spherical, and have a specific surface area of 1 to 20 m². 2 This invention provides a method for producing hollow spherical alumina particles, characterized by having a particle size of / g.
[0011] (raw materials) The following raw materials must be selected for use in the synthesis of the hollow spherical alumina particles of the present invention: (I) The basic aluminum lactate aqueous solution is controlled to contain 0-0.01% by mass of iron (Fe), 0-0.01% by mass of calcium (Ca), 0-0.01% by mass of magnesium (Mg), and 0-0.01% by mass of silicon (Si). (II) The basic aluminum lactate aqueous solution contains alkali metal element ions in an amount of 0.005 to 1.2% by mass, has a basicity of 60 to 80%, and contains Al in an amount of 8 to 13% by mass on an Al2O3 basis. (III) The basic aluminum lactate aqueous solution may be obtained by mixing an aluminum chloride solution with a sodium aluminate or potassium aluminate solution, or a combination thereof, and water to form an aluminum hydroxide gel, washing the gel with water, adding water to obtain an aluminum hydroxide slurry, and then adding lactic acid to react with it.
[0012] In this invention, a basic aluminum lactate aqueous solution is used as the main raw material, containing 0-0.01% by mass of iron (Fe), 0-0.01% by mass of calcium (Ca), 0-0.01% by mass of magnesium (Mg), and 0-0.01% by mass of silicon (Si). The alkali metal content is controlled, the basicity and aluminum content are controlled to a predetermined range, and the solution is spray-dried and calcined at a temperature of 1050°C to less than 1200°C for 2-8 hours. This makes it possible to provide hollow spherical alumina particles that meet predetermined particle size, specific surface area, drying loss, ignition loss, and bulk density specifications.
[0013] The present invention is manufactured using the materials described in (I), (II), and (III) above, and by the following manufacturing method.
[0014] (Manufacturing method) (Step 1) A basic aluminum lactate aqueous solution satisfying the requirements of (I) and (II) (and (III) if necessary) above is spray-dried and granulated in air or inert gas at a temperature of 180 to 280°C at a gas pressure of 0.4 to 1 MPa and an air flow rate of 200 to 4,000 L / min, with a liquid supply rate of 100 to 500 ml / min. Laser diffraction particle size distribution measurement of the dried granules shows that D50 is 1.0 to 4.5 μm, D90 is 8 μm or less, volatile matter is 0 to 10% by mass, and bulk density is 0.2 to 0.7 g / cm³. 3 To form a controlledly dried granule. (Step 2) Fill the calcination sheath with the dried granules obtained in Step 1 to a volume of 50-80% of the volume inside the sheath. (Step 3) The firing scabbard obtained in Step 2 is heated at a rate of 0.3 to 3°C / min, fired at a firing temperature within the range of 1,050°C to less than 1,200°C for 2 to 8 hours, and then cooled at a rate of 0.3 to 10°C / min in the atmosphere while introducing air at a rate of 50 to 200 ml / min.
[0015] The raw materials and manufacturing methods used for producing hollow spherical alumina particles are described in detail below.
[0016] (Basic aluminum lactate aqueous solution) The aqueous solution of basic aluminum lactate used in this invention has the following characteristics: (I) The basic aluminum lactate aqueous solution is controlled to contain 0-0.01% by mass of iron (Fe), 0-0.01% by mass of calcium (Ca), 0-0.01% by mass of magnesium (Mg), and 0-0.01% by mass of silicon (Si). (II) The basic aluminum lactate aqueous solution contains alkali metal element ions in an amount of 0.005 to 1.2% by mass, has a basicity of 60 to 80%, and contains Al in an amount of 8 to 13% by mass on an Al2O3 basis.
[0017] The basic aluminum lactate aqueous solution used in the present invention is controlled to contain 0-0.01% by mass of iron (Fe), 0-0.01% by mass of calcium (Ca), 0-0.01% by mass of magnesium (Mg), and 0-0.01% by mass of silicon (Si), as described in (I) above. If the Fe, Ca, Mg, and Si content in the basic aluminum lactate aqueous solution exceeds 0.01% by mass, it can cause the formation of different crystalline phases other than alumina during firing, or lead to defects such as discoloration. The Fe, Ca, Mg, and Si content is preferably 0.007% by mass or less, and more preferably 0.006% by mass or less, each.
[0018] The basic aluminum lactate aqueous solution used in the present invention must contain alkali metal element ions in an amount of 0.005 to 1.2% by mass, as described in (II) above. More preferably, it contains alkali metal element ions in an amount of 0.01 to 0.5% by mass. If the amount of alkali metal element ions is less than 0.005% by mass, the amount of alkali metal element ions is too low, and the temperature at which the phase transition to α-alumina occurs becomes high, and α-alumina will not be formed below 1200°C. On the other hand, if the amount of alkali metal element ions exceeds 1.2% by mass, the amount of alkali metal element ions is too high, and substances other than α-alumina, such as β-alumina, are formed, making it impossible to obtain the desired α-alumina.
[0019] The alkali metal element ions contained in the basic aluminum lactate aqueous solution used in this invention must be one or more selected from sodium and potassium.
[0020] The basic aluminum lactate aqueous solution used in this invention must have a basicity of 60-80% and contain 8-13% by mass of Al (in terms of Al2O3). If the basicity is less than 60%, there is a problem that the lactic acid content is too high and the solubility in water deteriorates. On the other hand, if it exceeds 80%, insoluble aluminum hydroxide precipitates, the liquid becomes cloudy, and hollow dry granules cannot be obtained when spray-dried. Also, if the Al content is less than 8% by mass (in terms of Al2O3), hollow dry granules cannot be obtained when dried by spray-drying. On the other hand, if it exceeds 13% by mass, the amount of Al is too high, resulting in poor storage stability, the formation of precipitates in the basic aluminum lactate aqueous solution, and making it unsuitable for spray-drying. The basicity of the basic aluminum lactate aqueous solution is preferably 62-78%, more preferably 64-76%. "Basicity" is a value that indicates what percentage of the valencies that can be substituted by a base are filled. Since aluminum is trivalent, if 2 / 3 (2 out of 3 valencies) is used, it means that the basicity is 66.66% (i.e., approximately 67%), and is measured in accordance with the method for measuring the basicity of liquid polyaluminum chloride for water supply, as specified in JIS K1475. The Al2O3 equivalent mass of aluminum (Al) in a basic aluminum lactate aqueous solution is more or less 8.5 to 12.5% by mass, more preferably 9 to 12% by mass. The Al2O3 equivalent mass of Al is commonly used when using aluminum salts, and the amount of aluminum is determined by converting it to the mass of Al2O3.
[0021] The aqueous solution of basic aluminum lactate used in the present invention is preferably obtained by the method described in (III). Specifically, (III) A basic aluminum lactate aqueous solution is obtained by mixing an aluminum chloride solution with a sodium aluminate or potassium aluminate solution or a combination thereof with water to form an aluminum hydroxide gel, washing the gel with water, adding water to obtain an aluminum hydroxide slurry, and then adding lactic acid to react with it. Of course, the basic aluminum lactate aqueous solution may be a basic aluminum lactate aqueous solution obtained by any method as long as it satisfies the above (I) and the above (II), but the basic aluminum lactate aqueous solution obtained in the above (III) is more preferable.
[0022] (Method for producing hollow spherical alumina particles) The hollow spherical alumina particles of the present invention are produced from the following Step 1 to Step 3: (Step 1) The basic aluminum lactate aqueous solution satisfying the requirements of the above (I) and (II) (and the above (III) as necessary) is subjected to spray drying for dry granulation at a gas pressure of 0.4 to 1 MPa, an air flow rate of 200 to 4,000 L / min, in air or an inert gas, at a temperature of 180 to 280°C, and a liquid supply rate of 100 to 500 ml / min. In the laser diffraction particle size distribution measurement of the dry granulated product, D50 is 1.0 to 4.5 μm, D90 is 8 μm or less, the volatile content is 0 to 10 mass%, and the bulk specific gravity is 0.2 to 0.7 g / cm 3 to form a dry granulated product controlled to the above values. (Step 2) Filling the dry granulated product obtained in Step 1 into a sagger for firing at 50 to 80% by volume of the internal volume of the sagger. (Step 3) Heating the sagger for firing obtained in Step 2 at a rate of 0.3 to 3°C / min, performing firing at a firing temperature within the temperature range of 1,050°C or higher and lower than 1,200°C for 2 to 8 hours, and then cooling at a rate of 0.3 to 10°C / min in the atmosphere while introducing air at 50 to 200 ml / min.
[0023] (Step 1) In Step 1, the basic aluminum lactate aqueous solution is subjected to spray drying for dry granulation at a gas pressure of 0.4 to 1 MPa, an air flow rate of 200 to 4,000 L / min, in air or an inert gas, at a temperature of 180 to 280°C, and a liquid supply rate of 100 to 500 ml / min. In the laser diffraction particle size distribution measurement of the dry granulated product, D50 is 1.0 to 4.5 μm, D90 is 8 μm or less, the volatile content is 0 to 10 mass%, and the bulk specific gravity is 0.2 to 0.7 g / cm 3A controlled dry granule is formed. If the gas pressure is less than 0.4 MPa, the gas pressure is too low, and it is not possible to obtain a dry granule with a D50 of 1.0 to 4.5 μm and a D90 of 8 μm or less in laser diffraction particle size distribution measurement. On the other hand, if it exceeds 1 MPa, a large compressor or pressure booster is required, which leads to poor productivity. The gas pressure is preferably 0.2 to 0.8 MPa, more preferably 0.3 to 0.7 MPa. If the air flow rate is less than 200 L / min, the air flow rate is too low, and it is not possible to obtain a fine granule. On the other hand, if it exceeds 4,000 L / min, a large compressor is required, which leads to poor productivity. The air flow rate is preferably 300 to 3,500 L / min, more preferably 500 to 3,000 L / min.
[0024] Step 1 involves drying and granulating in air or an inert gas, where the inert gas may be a noble gas (e.g., helium, neon, or argon) or nitrogen gas. It is usually carried out in air. The drying temperature is 180-280°C, preferably 190-260°C. Drying and granulating at temperatures below 180°C results in a high moisture content in the dried material, making it prone to agglomeration in the dry state and preventing the formation of independent, hollow, spherical alumina after calcination. Drying and granulating at temperatures above 280°C causes some of the organic components of basic aluminum lactate to oxidize, resulting in browning of the dried material, deterioration of its physical properties, and collapse of its spherical shape during calcination.
[0025] If the liquid supply rate is less than 100 ml / min, there is a problem that productivity will be reduced due to insufficient liquid supply. If it exceeds 500 ml / min, there is a problem that the granules will become too large, making it impossible to obtain granules with the desired particle size, and the volatile content will exceed 10% by mass.
[0026] Dry granulation is performed using spray drying. To ensure that the D50 and D90 values of the dried granules are within a predetermined range, methods such as using a two-fluid nozzle or a four-fluid nozzle are employed. Of course, any drying granulation method can be used as long as the D50 and D90 values, which represent the particle size of the dried granules, are within the predetermined range.
[0027] The dried granules have a D50 size of 1.0-4.5 μm and a D90 size of 8 μm or less, with a volatile content of 0-10% by mass and a bulk density of 0.2-0.7 g / cm³. 3 It is necessary to control this. D50 and D90 are obtained by dry measurement using a laser diffraction particle size analyzer (Malvern Panalytical Mastersizer 3000), as will be explained later in the description of D50 and D90 of the final hollow spherical alumina particles. D50 means that half of the population has a diameter below this value, and D90 means that 90% of the population has a diameter below this value. If D50 is less than 1.0, the particles are highly cohesive and difficult to use in a dispersed state, and if D50 is greater than 4.5 μm, the applications for use as a filler for dielectric constant adjustment in thin-layer resin sheets or as a filler for dielectric constant adjustment in heat dissipation fillers of thin-layer resin sheets are narrowed. The D50 of the dried granules is preferably 1.2 to 4.0 μm, more preferably 1.5 to 3.0 μm. The D90 of the dried granules is preferably 5.0 to 7.5 μm, more preferably 5.5 to 6.5 μm.
[0028] The dried granules obtained in step 1 have a volatile content of 0-10% by mass and a bulk density of 0.2-0.7 g / cm³. 3 The volatile content is controlled to the extent that the drying is insufficient and the moisture content of the dried material is high, which makes it prone to agglomeration in the dry state and has the disadvantage of not forming independent hollow spherical alumina after calcination. It is preferable that the volatile content be 0% by mass. The volatile content is preferably 1.0 to 9.0% by mass, more preferably 2.0 to 8.0% by mass. The bulk density of the dried granules is 0.20 to 0.7 g / cm³. 3 Preferably 0.25 to 0.65 g / cm³ 3 , more preferably 0.3 to 0.6 g / cm³ 3 Its bulk density is 0.2 g / cm³. 3 Smaller particles have the disadvantage of reduced strength due to increased hollowness and thinner outer shell, resulting in a lower hollow spherical alumina particle size of 0.70 g / cm³. 3If the size is larger, the degree of hollowness during granulation decreases, and the thickness of the outer shell increases, making it more prone to deformation and making it difficult to form a spherical shape. Volatile content is measured using an A&D MX50 heated dry moisture meter under the condition of 105°C for 30 minutes. Bulk density is the value obtained by dividing mass by volume. In the embodiment of the present invention, a sample of approximately 40 g (M) of powder that has been sieved through a 1 mm mesh opening and weighed with an accuracy of 0.1 mass%, is placed in a 100 ml graduated cylinder (minimum scale unit 1 ml), the surface is lightly leveled, the loose bulk volume (V0) is read, and the bulk density: M / V0 (g / cm³) 3 The volatility can be adjusted by the temperature and liquid delivery rate during granulation, and the bulk density can be controlled by the gas pressure during spray granulation.
[0029] (Process 2) In step 2 of the method for producing hollow spherical alumina particles of the present invention, the dried granules obtained in step 1 are placed in a firing sheath and filled to 50 to 80% of the sheath's internal volume. If the amount of material filling the firing sheath is less than 50% of the internal volume, the amount of material added during firing will be small, resulting in poor productivity. If it exceeds 80% of the internal volume, an incompletely fired portion will remain on the bottom surface of the sheath during firing, making stable firing impossible. The amount of material filling the firing sheath is preferably 55 to 75% of the internal volume, more preferably 60 to 70% of the internal volume. The firing sheath is not particularly limited as long as it can withstand the firing conditions, but alumina or mulyde-kojilite is preferred. When using alumina or mulyde-kojilite, the firing sheath does not deform within the firing temperature range, and different crystalline phases do not form due to elemental transfer from the firing sheath to the hollow spherical alumina.
[0030] (Step 3) In step 3 of the method for producing hollow spherical alumina particles of the present invention, the calcination sheath obtained in step 2 is heated at a rate of 0.3 to 3°C / min, calcined at a calcination temperature in the range of 1,050°C to less than 1,200°C for 2 to 8 hours, and then cooled at a rate of 0.3 to 10°C / min in the atmosphere while introducing air at a rate of 50 to 200 ml / min.
[0031] If the heating rate in step 3 is less than 0.3°C / min, the time required for heating is too long, resulting in decreased productivity. If it exceeds 3°C / min, variations in firing occur in the powder within the sheath, making it impossible to obtain stable hollow spherical alumina particles. The heating rate is preferably 0.5 to 2.8°C / min, and more preferably 1.0 to 2.5°C / min. If the firing temperature is less than 1050°C, firing is insufficient, and crystalline phases other than α-alumina remain. If the firing temperature exceeds 1200°C, a firing furnace with heat-resistant measures becomes necessary, resulting in decreased productivity. The firing temperature is preferably 1070 to 1190°C, and more preferably 1090 to 1180°C. If the firing time is less than 2 hours, firing is insufficient, and crystalline phases other than α-alumina remain. If it exceeds 8 hours, there is a problem of decreased productivity. The firing time is preferably 2.5 to 7.5 hours, and more preferably 3.0 to 7.0 hours.
[0032] During cooling, it is necessary to cool at a rate of 0.3 to 10°C / min. If the cooling rate is less than 0.3°C / min, the time required for cooling becomes too long, resulting in a decrease in productivity. If it exceeds 10°C / min, the sheath breaks due to thermal stress, making it impossible to recover the hollow spherical alumina particles that have been sintered stably. The cooling rate is preferably 0.5 to 2.8°C / min, more preferably 1.0 to 2.5°C / min.
[0033] In the firing furnace, it is necessary to introduce air at a rate of 50-200 ml / min from the atmosphere during heating, firing, and cooling. If the air introduction rate is less than 50 ml / min, the amount of air introduced is too little, resulting in insufficient firing of the bottom surface of the sheath and causing firing defects. On the other hand, if the air introduction rate exceeds 200 ml / min, the amount of air introduced is too much when firing at a temperature of 1050-1200°C for 2-8 hours, causing the furnace to cool down too much and preventing the maximum firing temperature from being reached, resulting in sintering defects. The air introduction rate is preferably 60-180 ml / min, more preferably 70-170 ml / min.
[0034] (Hollow spherical alumina particles) The hollow spherical alumina particles of the present invention are manufactured by the above steps 1 to 3. The hollow spherical alumina particles obtained by this method have a particle size distribution of D50 of 1.0 to 3.5 μm and a D90 of 6 μm or less, and are spherical, hollow alumina particles with a specific surface area of 1 to 20 m². 2 The value is / g, and the crystalline system (also called the crystalline phase) exhibits the α phase.
[0035] The particle size distribution is obtained by dry measurement using a laser diffraction particle size analyzer (Malvern Panalytical Mastersizer 3000). Figure 1 shows the particle size distribution results for alumina particles in Example 1. In the particle size distribution, D50 means that half of the population has a diameter below this value, and D90 means that 90% of the population has a diameter below this value. As shown in Figure 1, the particle size distribution of alumina particles in Example 1 was confirmed to have a D50 of 2.5 μm and a D90 of less than 6 μm. When D50 is less than 1.0 μm, aggregation becomes strong and dispersion becomes difficult, and when D50 exceeds 3.5 μm, it becomes difficult to use as a filler for dielectric constant adjustment in thin-layer resin sheets or as a heat dissipation filler in thin-layer resin sheets. Furthermore, when D90 exceeds 6 μm, the range of applications for use as a filler for dielectric constant adjustment in thin-layer resin sheets or as a heat dissipation filler in thin-layer resin sheets becomes narrower.
[0036] The alumina particles obtained by the manufacturing method of the present invention are spherical and hollow inside. "Hollow" does not mean perfectly spherical hollow, as stated in the definition of the term, but includes, for example, those that appear to have a cavity despite being spherical (Figure 4), as shown in the electron microscope images of the alumina particles of Example 1 in Figures 4 and 5, as well as those that are not fully spherical and remain in a cage-like shape.
[0037] The hollow spherical alumina particles obtained by the manufacturing method of the present invention have a specific surface area of 1 to 20 m². 2The specific surface area is 1 m² / g and the crystal system exhibits the α phase. Specific surface area is the surface area per unit mass or per unit volume of an object. In this invention, the specific surface area is measured in N2 using an automatic specific surface area measuring device (Gemini7 2390, manufactured by Shimadzu Corporation), and the data analyzed by the BET method is used. The specific surface area of the alumina particles in this invention is 1 m² / g. 2 If the value is less than / g, the specific surface area is too small, resulting in fewer adsorption sites when performing surface treatment using dispersants, etc., making surface treatment difficult. 2 If the specific surface area is greater than / g, there is a drawback that too much nitrogen gas (N2) is adsorbed on the alumina surface, resulting in insufficient crystal growth as α-alumina. The specific surface area of the hollow spherical alumina particles of the present invention is preferably 3 to 15 m². 2 / g, comfortably 5-13m 2 The weight is per gram. The crystal system of the hollow spherical alumina particles of this invention is α-type. This invention does not anticipate the presence of other crystal systems of alumina particles, such as γ-type. The crystal system is mainly determined by measuring it using the θ / 2θ method with a Cu target using an X-ray diffractometer (specifically, a MiniFlex manufactured by Rigaku Corporation).
[0038] The hollow spherical alumina particles in this application have a bulk density of 0.3 to 0.7 g / cm³. 3 This is preferable. More preferably 0.45 to 0.65 g / cm³. 3 Therefore, if the bulk density is less than 0.3, the outer layer becomes too thin and cannot maintain its shape as hollow spherical alumina particles. On the other hand, if the bulk density is 0.7 g / cm³ 3 Beyond a certain point, the outer layer becomes too thick, and the particles cease to function as hollow, spherical alumina particles. Bulk density is the value obtained by dividing mass by volume. Specifically, a sample of approximately 40g (M) of powder, sieved through a 1mm mesh and weighed with an accuracy of 0.1% by mass, is placed in a 100ml graduated cylinder (minimum increment of 1ml), the surface is lightly leveled, and the loose bulk volume (V0) is read. Bulk density: M / V0 (g / cm³) 3 ) is being calculated.
[0039] In this invention, the hollow spherical alumina particles must have an α-phase crystalline structure. If the α-phase is not formed, the relative permittivity at a frequency f=1MHz measured by the capacitance method will not satisfy the range of 1.7 to 2.4. The relative permittivity at f=1MHz was measured by the capacitance method using the WKR6510P dielectric constant measurement system (manufactured by Toyo Technica Co., Ltd.). If the relative permittivity is less than 1.7, the air content is too high, and the shape of the hollow spherical alumina particles cannot be maintained. If it exceeds 2.4, the dielectric constant is too high, and it cannot be used as a low relative permittivity material. If the relative permittivity is high, when a high frequency is applied after being incorporated into a resin thin film, it may generate heat, making it unsuitable for use in resin thin films. The relative permittivity at f=1MHz is preferably 1.75 to 2.3, more preferably 1.8 to 2.2.
[0040] (Examples) The present invention will be described in more detail by reference to examples. The present invention should not be construed as being limited to these examples. In the examples, unless otherwise specified, percentages and parts are based on mass.
[0041] (Example 1) First, a 10L jacketed glass-lined (GL) stirring vessel was used, and cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the vessel and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0042] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel and 162.1 g of tap water were added and stirred for 30 minutes to obtain a slurry of 265.4 g. 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ion: 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0043] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160: manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air flow rate of 300 L / min, using a two-fluid nozzle to obtain collected dried granules (volatile content: 6.8 mass%). The obtained dried granules were packed into a calcined alumina sheaths at 60 volume%. Next, the temperature was increased at 1°C / min, and calcination was performed by holding the peak calcination condition at 1100°C for 5 hours, followed by cooling at a rate of 1°C / min to obtain hollow spherical alumina particles. The amount of air introduced during heating, holding, and cooling (corresponding to introducing air at "50-200 ml / min" in the third step) was kept constant at 100 ml / min.
[0044] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 1. The particle size distribution was the same as that used for the measurement of hollow spherical alumina particles D50 and D90 described later, and was measured dry using a laser scattering particle size analyzer (Malvern Panalytical Mastersizer 3000). D50 means that half of the population has a diameter below this value, and D90 means that 90% of the population has a diameter below this value.
[0045] Furthermore, the particle size distribution of the obtained alumina particles was measured, and D50 and D90 were determined and listed in Table 5. The particle size distribution was measured dry using a laser scattering particle size analyzer (Malvern Panalytical Mastersizer 3000). Figure 1 shows the particle size distribution results of the alumina particles of Example 1 in a graph. As mentioned above, D50 means that half of the population has a diameter below this value, and D90 means that 90% of the population has a diameter below this value. As shown in Figure 1, it was confirmed that the particle size distribution of the alumina particles of Example 1 had a D50 of 2.5 μm and a D90 of 5.0 μm or less.
[0046] Table 1 shows the specific surface area (m²) of the obtained alumina particles. 2 (g), bulk density (g / cm³) 3 The crystalline structure, relative permittivity at f=1MHz, and the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) are also listed. The specific surface area was measured in N2 using an automatic specific surface area measuring device (Shimadzu Corporation Gemini7 2390) and the data shown is analyzed by the BET method. The bulk density is the value obtained by dividing the mass by the volume. Specifically, a sample of approximately 40g (M) of powder that has been sieved through a 1mm mesh and weighed with an accuracy of 0.1 mass%, was placed in a 100ml graduated cylinder (minimum increment of 1ml), the surface was lightly leveled, and the loose bulk volume (V0) was read, and the bulk density was calculated as: M / V0 (g / cm³). 3 The following was calculated. The crystal system (crystal phase) was measured using the θ / 2θ method with a Cu target using an X-ray diffractometer (MiniFlex, Rigaku Corporation) and is shown in Table 1. The relative permittivity at f=1MHz was measured using the capacitance method with a dielectric constant measurement system WKR6510P (Toyo Technica Corporation). The content of Na, K, Ca, Si, Mg, and Fe was measured using energy-dispersive X-ray fluorescence analysis (EDX) with a desktop scanning electron microscope (SEM: JEOL Ltd. JCM-7000). Figure 2 shows the measurement results of the crystal system of the alumina particles obtained in Example 1.
[0047] From the X-ray diffraction results of the alumina particles in Example 1 shown in Figure 2, it was confirmed that α-alumina was formed from the alumina particles in Example 1. Furthermore, when the relative permittivity of the alumina particles was measured at f=1MHz using the capacitance method, it was confirmed that the relative permittivity was 2.0.
[0048] Figures 4 and 5 show SEM images of the alumina particles from Example 1, measured using a field emission scanning electron microscope (FE-SEM: JSM-7001F, JEOL Ltd.). Figure 4 is a 50,000x SEM image, confirming that α-alumina microcrystals aggregate to form the outer skin of hollow spherical alumina. Figure 5, a 50,000x SEM image of the cross-section of the alumina particles from Example 1, confirms that the hollow spherical alumina particles have a spherical structure. Therefore, it was confirmed that the alumina particles obtained in Example 1 are hollow spherical alumina particles.
[0049] (Example 2) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0050] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ion: 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0051] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air flow rate of 300 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 7.1 mass%) were then packed into a calcined alumina sheath at 70 volume percent. Next, the calcined sheath was heated at 1°C / min, maintained at a peak calcination condition of 1170°C for 5 hours, and then cooled at 1°C / min. This yielded hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0052] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 1. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 5. In Table 5, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0053] (Example 3) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0054] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ions: 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0055] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 118°C, a gas pressure of 0.5 MPa, a liquid supply rate of 150 ml / min, and an air supply rate of 350 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 6.0 mass%) were packed into a calcined alumina sheath at 60 volume%, and the temperature was increased at 1°C / min, maintained at a peak calcination condition of 1100°C for 6 hours, and then cooled at 1°C / min to perform calcination, obtaining hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake rate was kept constant at 85 ml / min during the heating, holding, and cooling periods.
[0056] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 1. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 5. In Table 5, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0057] (Example 4) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1531.6g of tap water was added to the kettle and stirred while simultaneously adding 1909.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1559.0g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 20.0% by mass, Na content equivalent to Na2O: 18.9%) to obtain 5000g of aluminum hydroxide gel solution.
[0058] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 1920 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 159.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 262.3 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.9 mass%, basicity: 71.5%, sodium ions: 0.04 mass%, Si: 0.0048 mass%, Ca: 0.0038 mass%, Mg: 0.001 mass%, Fe: 0.001 mass%).
[0059] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air supply rate of 300 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 6.5 mass%) were packed into a calcined alumina sheath at 70 volume%, and the temperature was increased at 1°C / min, maintained at a peak calcination condition of 1170°C for 5 hours, and then cooled at 1°C / min to perform calcination, obtaining hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake rate was kept constant at 100 ml / min during the heating, holding, and cooling phases.
[0060] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 1. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 5. In Table 5, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0061] (Example 5) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0062] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ion: 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0063] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 118°C, a gas pressure of 0.5 MPa, a liquid supply rate of 150 ml / min, and an air supply rate of 350 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 6.9 mass%) were packed into a calcined mullite cordierite sheath at 60 volume%, and calcination was performed by raising the temperature at 2°C / min, followed by peak calcination conditions of 1100°C for 6 hours, and then cooling at 2°C / min to obtain hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake rate was kept constant at 100 ml / min during heating, holding, and cooling.
[0064] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 2. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 6. In Table 6, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0065] (Example 6) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0066] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ion: 0.01 mass%, Si: 52 ppm, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0067] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (MDP-050, manufactured by GF Co., Ltd.) with an inlet temperature of 200°C, an outlet temperature of 100°C, a gas pressure of 0.5 MPa, a liquid supply rate of 650 ml / min, and an air supply rate of 1000 L / min using a four-fluid nozzle. The collected dried granules (volatile content: 6.6 mass%) were packed into a calcined alumina sheath at 60 volume%, and the temperature was increased at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, followed by cooling at 1°C / min to obtain hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0068] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 2. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 6. In Table 6, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0069] (Example 7) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0070] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of the basic aluminum lactate aqueous solution of the present invention (Al amount in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ions: 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0071] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (MDP-050, manufactured by GF Co., Ltd.) with an inlet temperature of 180°C, an outlet temperature of 101°C, a gas pressure of 0.5 MPa, a liquid supply rate of 500 ml / min, and an air supply rate of 1,000 L / min, using a four-fluid nozzle. The collected dried granules (volatile content: 7.6 mass%) were packed into a calcined alumina sheath at 60 volume%, and the temperature was increased at 1°C / min, followed by peak calcination under conditions of 1100°C for 5 hours, followed by cooling at 1°C / min to obtain hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0072] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 2. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 6. In Table 6, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0073] (Example 8) First, a jacketed GL stirring kettle with a capacity of 1 L was used, and cooling water at 5°C was circulated through the jacket. Next, 153.1 g of tap water was added to the kettle and stirred, while simultaneously adding 190.4 g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%), 153.9 g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 20.0% by mass, Na content equivalent to Na2O: 18.9%), and 2 g of potassium aluminate powder to obtain 500 g of aluminum hydroxide gel solution.
[0074] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated five times. The resulting washing gel was 195 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.7 g of the obtained washing gel, followed by 156.6 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 260.3 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 1.5 hours, it was slowly cooled to prepare 300 g of basic aluminum lactate aqueous solution (Al content 8.8 mass%, basicity 72.4%, sodium ions 0.02 mass%, potassium ions 0.01 mass%, Si: 0.0047 mass%, Ca: 0.0050 mass%, Mg: 0.0006 mass%, Fe: 0.0011 mass%).
[0075] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air supply rate of 300 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 7.0 mass%) were packed into a calcined alumina sheath at 60 volume%, and the temperature was increased at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, followed by cooling at 1°C / min to obtain hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake rate was kept constant at 100 ml / min during heating, holding, and cooling.
[0076] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 2. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 6. In Table 6, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0077] (Comparative Example 1) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0078] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel and then 162.1 g of tap water were added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of basic aluminum lactate aqueous solution (Al content 8.4 mass%, basicity 70.3%, sodium ion 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0079] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by PRISCO Corporation) at an inlet temperature of 250°C, an outlet temperature of 105°C, a liquid supply rate of 400 ml / min, and an atomizer at 18,000 rpm. The collected dried granules (volatile content: 7.3% by mass) were packed into a calcined alumina sheath at 60% by volume, and calcination was carried out by increasing the temperature at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, and then decreasing the temperature at 1°C / min. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0080] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 3. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 7. In Table 7, the content of impurities in the obtained alumina particles, namely sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe), is also recorded in the same manner as in Example 1.
[0081] In Comparative Example 1, as shown in Table 3, the D50 of the dried granules of the basic aluminum lactate aqueous solution was 49 μm and the D90 was 110 μm, failing to satisfy the requirements of the present invention for dried granules to be D50 (1 to 4.5 μm) and D90 (8 μm or less). The final hollow spherical alumina particles also had a D50 of 43 μm and a D90 of 105 μm, failing to satisfy the requirements of the present invention for D50 (1.0 to 3.5 μm) and D90 (6 μm or less), and thus the particle size of the hollow spherical alumina particles could not be reduced. This is thought to be due to the use of an atomizer that could not produce small dried granules in the drying granulation of the basic aluminum lactate aqueous solution. In spray drying, changing the droplet-forming part from a nozzle to an atomizer increases productivity, but it makes it impossible to produce large droplets, i.e., fine droplets.
[0082] (Comparative Example 2) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0% by mass, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0% by mass, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0083] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of basic aluminum lactate aqueous solution (Al content 8.4 mass%, basicity 70.3%, sodium ion 0.01 mass%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0084] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 150°C, an outlet temperature of 85°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air supply rate of 300 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 13.4 mass%) were filled into a calcined alumina sheath at 60 volume%, and calcination was carried out by raising the temperature at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, and then cooling at 1°C / min. The air intake rate was kept constant at 100 ml / min during heating, holding, and cooling.
[0085] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 3. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 7. In Table 7, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0086] In Comparative Example 2, as shown in Table 3, the D50 of the dried granules of the basic aluminum lactate aqueous solution was 130 μm and the D90 was 8800 μm, failing to satisfy the requirements of the present invention for dried granules to be D50 (1 to 4.5 μm) and D90 (8 μm or less). The final hollow spherical alumina particles also had a D50 of 125 μm and a D90 of 865 μm, failing to satisfy the requirements of the present invention for D50 (1.0 to 3.5 μm) and D90 (6 μm or less), and thus the particle size of the hollow spherical alumina particles could not be reduced. This is thought to be because the inlet temperature of the spray dryer was 150°C and the outlet temperature was 85°C, which is outside the temperature range of 180°C to 280°C used during spray drying. As a result, the volatile content of the dried aluminum lactate granules increased, causing powder to adhere (aggregate) before firing, and the aggregates were fired as they were, resulting in larger particle sizes.
[0087] (Comparative Example 3) First, a 10L jacketed GL stirring kettle was used, and 5°C cooling water was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0 wt%, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0 wt%, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0088] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of basic aluminum lactate aqueous solution (Al content in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ions: 0.01 wt%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0089] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air flow rate of 300 L / min, using a two-fluid nozzle. The collected dried granules (volatile content: 6.8 mass%) were filled into a calcined alumina sheath at 95 volume%, and the temperature was increased at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, and then cooling at 1°C / min. The air intake was kept constant at 100 ml / min during the heating, holding, and cooling periods.
[0090] The particle size distribution of the dried granules before calcination was measured, and D50 and D90 were determined and recorded in Table 3. Although calcination was performed, it was impossible to measure D50, D90, and other values of the alumina particles obtained due to insufficient calcination. This was confirmed to be because the amount of dried granules filling the calcination scabbard was too high at 95% by volume during calcination, resulting in insufficient calcination, the generation of a large amount of residual carbon, and the material not becoming alumina.
[0091] (Comparative Example 4) First, a 10L jacketed GL stirring kettle was used, and 5°C cooling water was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0 wt%, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0 wt%, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0092] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of basic aluminum lactate aqueous solution (Al content in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ions: 0.01 wt%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0093] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by PRISCO Corporation) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air flow rate of 300 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 6.8 mass%) were filled into a calcined alumina sheath at 60 volume%, and calcination was carried out by raising the temperature at 1°C / min, followed by peak calcination conditions of 800°C for 5 hours, and then lowering the temperature at 1°C / min. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0094] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 3. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 7. In Table 7, the content of impurities such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe) in the obtained alumina particles is also recorded in the same manner as in Example 1.
[0095] In this case, since the firing temperature is 800°C, which is lower than 1050°C, the resulting alumina particles have a γ crystal system instead of α, resulting in a higher specific surface area.
[0096] (Comparative Example 5) First, a 10L jacketed GL stirring kettle was used, and 5°C cooling water was circulated through the jacket. Next, 1451.1g of tap water was added to the kettle and stirred while simultaneously adding 1911.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0 wt%, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0 wt%, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0097] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 162.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 265.4 g. Next, 39.7 g of lactic acid (90% lactic acid) was added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, it was slowly cooled to prepare 300 g of basic aluminum lactate aqueous solution (Al content in terms of Al2O3: 8.4 mass%, basicity: 70.3%, sodium ions: 0.01 wt%, Si: 0.0052 mass%, Ca: 0.0043 mass%, Mg: 0.0009 mass%, Fe: 0.0015 mass%).
[0098] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 108°C, a gas pressure of 0.2 MPa, a liquid supply rate of 200 ml / min, and an air flow rate of 150 L / min, using a two-fluid nozzle. The collected dried granules (volatile content: 7.3 mass%) were packed into a calcined alumina sheath at 70 volume%, and calcination was performed by increasing the temperature at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, and then decreasing the temperature at 1°C / min, to obtain hollow spherical alumina particles exhibiting the α-phase crystalline phase. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0099] The particle size distribution of the dried granules before firing was measured, and D50 and D90 were determined and recorded in Table 4. The particle size distribution (D50 and D90), specific surface area, bulk density, crystal system, and dielectric constant at f=1MHz of the obtained alumina particles were measured using the method described in Example 1, and the results are recorded in Table 8. In Table 8, the content of impurities in the obtained alumina particles, namely sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silicon (Si), and iron (Fe), is also recorded in the same manner as in Example 1.
[0100] In Comparative Example 5, the gas pressure during spray drying was low at 0.2 MPa and the air flow rate was also low at 150 L / min, making it impossible to produce fine aluminum lactate granules when using a two-fluid nozzle for spray drying. This is evident from Table 4, where the resulting hollow spherical alumina particles have large particle sizes, with a D50 of 12 μm and a D90 of 34 μm. Comparative Example 5 corresponds to the alumina particles described in Patent Document 1.
[0101] (Comparative Example 6) Using a 10L jacketed GL stirring kettle, first, cooling water at 5°C was circulated through the jacket. Next, 1429.8g of tap water was added to the kettle and stirred while simultaneously adding 1909.4g of aluminum chloride aqueous solution (Al content equivalent to Al2O3: 10.0 wt%, basicity: 2.4%) and 1660.8g of sodium aluminate aqueous solution (Al content equivalent to Al2O3: 23.0 wt%, Na content equivalent to Na2O: 18.0%) to obtain 5000g of aluminum hydroxide gel solution.
[0102] Next, the obtained gel solution was dehydrated using a centrifugal dehydrator, and the process of adding water and stirring was repeated seven times. The amount of washing gel obtained was 2190 g. Next, using a 1 L glass separable flask placed on a mantle heater, 103.2 g of the obtained washing gel, followed by 152.1 g of tap water, was added and stirred for 30 minutes to obtain a slurry of 255.3 g. Next, 34.7 g of lactic acid (90% lactic acid) and 10.0 g of calcium chloride were added to the obtained slurry, and after heating and stirring at 100°C for 3 hours, slow cooling was performed to prepare 300 g of basic aluminum lactate aqueous solution (Al amount equivalent to Al2O3: 8.2 mass%, basicity: 70.5%, sodium ion: 0.01 wt%, Si: 0.0050 mass%, Ca: 1.26 mass%, Mg: 0.0007 mass%, Fe: 0.0015 mass%).
[0103] The obtained basic aluminum lactate aqueous solution was granulated and dried using a spray dryer (TR-160, manufactured by Pris Co., Ltd.) with an inlet temperature of 250°C, an outlet temperature of 115°C, a gas pressure of 0.5 MPa, a liquid supply rate of 200 ml / min, and an air flow rate of 300 L / min using a two-fluid nozzle. The collected dried granules (volatile content: 7.4 mass%) were filled into a calcined alumina sheath at 60 volume%, and calcination was carried out by raising the temperature at 1°C / min, followed by peak calcination conditions of 1100°C for 5 hours, and then lowering the temperature at 1°C / min. The air intake was kept constant at 100 ml / min during heating, holding, and cooling.
[0104] In Comparative Example 6, the high content of Ca as an impurity resulted in the formation of a crystalline phase that was not α-alumina during calcination, thus failing to obtain the hollow spherical alumina particles desired by the present invention. This is described in Table 8. Figure 3 shows the results of X-ray diffraction measurements of the alumina particles obtained in Comparative Example 6 using a Rigaku MiniFlex X-ray diffractometer with a Cu target using the θ / 2θ method. The X-ray diffraction peak pattern in Figure 3 differs significantly from that in Figure 2, indicating that it is not an α-alumina crystalline system.
[0105] [Table 1]
[0106] [Table 2]
[0107] [Table 3]
[0108] [Table 4]
[0109] [Table 5]
[0110] [Table 6]
[0111] [Table 7]
[0112] [Table 8]
[0113] In Tables 5-8, "nd" indicates that measurement was not possible.
[0114] As shown in Tables 1-2, the D50 and D90 values in the particle size distribution of the dried granules of the basic aluminum lactate aqueous solution obtained during the production of hollow spherical alumina particles in Examples 1-8 were confirmed to be in the range of 1.0-4.5 μm for D50 and 8 μm or less for D90. Furthermore, as shown in Tables 5 and 6, the hollow spherical alumina particles shown in Examples 1-8 all exhibited α-alumina, and particle size distribution measurements confirmed that D50 was 1.0-3.5 μm and D90 was 6 μm or less. In addition, the specific surface area was 1-20 m². 2 It was confirmed that the concentration was / g. Furthermore, elemental analysis of these hollow spherical alumina particles using energy-dispersive X-ray fluorescence revealed that they contained alkali metal element ions (Na and K) in the range of 0.005 to 1.2 mass%, while the concentrations of Ca, Mg, Si, and Fe were undetectable. In addition, Tables 5 and 6 show that the relative permittivity at a frequency f=1MHz, measured by the capacitance method, was within the range of 1.7 to 2.4, indicating that when mixed into a thin film resin sheet, it is possible to achieve both small particle size and low relative permittivity.
[0115] As shown in Tables 3 and 7, Comparative Example 1 uses an atomizer in the granulation portion of the spray drying process. As a result, the D50 is 43 μm and the D90 is 105 μm in the laser diffraction particle size distribution measurement of the dried granules, which are large. Because it is not possible to produce fine droplets, it is not possible to produce dried granules with small particle sizes. Therefore, even after calcination, it is not possible to obtain hollow spherical alumina with fine particle sizes. In Comparative Example 2, the inlet and outlet temperatures of the spray drying process are low, resulting in high volatile content in the dried aluminum lactate granules and the observation of numerous aggregates due to adhesion. When these are placed in a calcination sheath and calcined, hollow spherical alumina remains in the form of aggregated clumps, thus failing to obtain the small particle size (D50 of 1.0 to 3.5 μm, D90 of 6 μm or less) that is the objective of the present invention. In Comparative Example 3, the dried aluminum lactate granules are excessively filled into the calcination sheath at 95 volume percent before calcination, resulting in areas that are not calcined sufficiently and residual charcoal remaining, thus resulting in a calcination failure. Comparative Example 4 has a problem in that the calcination temperature during the firing of the dried granules is 800°C, which is lower than 1050°C, resulting in a γ phase with a large specific surface area in the crystalline system and not the α phase. Comparative Example 5 has a problem in that the gas pressure and air flow rate during spray drying are low, making it impossible to obtain dried granules with small particle sizes. As a result, even after calcination, hollow spherical alumina with small particle sizes (D50 of 1.0 to 3.5 μm, D90 of 6 μm or less), which is the objective of the present invention, cannot be obtained. Comparative Example 6 has too much Ca content, so a composite oxide of aluminum and calcium is formed and it is not a single phase of α alumina.
[0116] The present invention also proposes the following embodiments. [1] A basic aluminum lactate aqueous solution was spray-dried and granulated in air or inert gas at a gas pressure of 0.4 to 1 MPa and an air flow rate of 200 to 4,000 L / min at a temperature of 180 to 280°C, with a liquid supply rate of 100 to 500 ml / min. Laser diffraction particle size distribution measurement of the dried granules showed a D50 of 1.0 to 4.5 μm, a D90 of 8 μm or less, a volatile content of 0 to 10% by mass, and a bulk density of 0.2 to 0.7 g / cm³. 3 A first step of forming a controlled hollow dry granule, The second step involves filling a calcination sheath with 50-80% of the volume of the sheath's internal volume using the dried granules obtained in the first step, A method for producing hollow spherical alumina particles, comprising: raising the temperature of the firing sheath obtained in the second step at 0.3 to 3°C / min, firing it at a firing temperature in the temperature range of 1,050°C to less than 1,200°C for 2 to 8 hours, and then lowering the temperature in the atmosphere at 0.3 to 10°C / min while introducing air at 50 to 200 ml / min, The basic aluminum lactate aqueous solution contains iron (Fe) in amounts of 0-0.01% by mass, calcium (Ca) in amounts of 0-0.01% by mass, magnesium (Mg) in amounts of 0-0.01% by mass, and silicon (Si) in amounts of 0-0.01% by mass, and also contains alkali metal element ions in amounts of 0.005-1.2% by mass, has a basicity of 60-80%, and contains aluminum in amounts of 8-13% by mass on an Al2O3 basis. The hollow spherical alumina particles, as measured by laser diffraction particle size distribution analysis, have a D50 of 1.0 to 3.5 μm and a D90 of 6 μm or less, are hollow inside and spherical, and have a specific surface area of 1 to 20 m². 2 A method for producing hollow spherical alumina particles, characterized by having a density of / g. [2] The hollow spherical alumina particles have a bulk density of 0.3 to 0.7 g / cm³. 3 A method for producing hollow spherical alumina particles as described in [1], characterized in that the crystalline phase of the hollow spherical alumina particles is the α phase. [3] The method for producing hollow spherical alumina particles according to [1] or [2], characterized in that the hollow spherical alumina particles exhibit a relative permittivity of 1.7 to 2.4 at a frequency f=1MHz measured by the capacitance method. [4] The method for producing hollow spherical alumina particles according to any one of [1] to [3], characterized in that the basic aluminum lactate aqueous solution is obtained by mixing an aluminum chloride solution with either or both sodium aluminate and potassium aluminate and water to form an aluminum hydroxide gel, washing the obtained gel with water, adding water to obtain an aluminum hydroxide slurry, and then adding lactic acid and reacting it.
Claims
1. A basic aluminum lactate aqueous solution was spray-dried and granulated in air or an inert gas at a gas pressure of 0.4 to 1 MPa and an air flow rate of 200 to 4,000 L / min at a temperature of 180 to 280°C, with a liquid supply rate of 100 to 500 ml / min. Laser diffraction particle size distribution measurement of the dried granules showed a D50 of 1.0 to 4.5 μm, a D90 of 8 μm or less, a volatile content of 0 to 10% by mass, and a bulk density of 0.2 to 0.7 g / cm³. 3 A first step of forming a controlled hollow dry granule, The second step involves filling a calcination sheath with the dried granules obtained in the first step, at a volume of 50 to 80 percent of the volume inside the sheath. A method for producing hollow spherical alumina particles, comprising: raising the temperature of the firing sheath obtained in the second step at 0.3 to 3°C / min, firing it at a firing temperature in the temperature range of 1,050°C to less than 1,200°C for 2 to 8 hours, and then lowering the temperature in the atmosphere at 0.3 to 10°C / min while introducing air at 50 to 200 ml / min, The basic aluminum lactate aqueous solution contains iron (Fe) in amounts of 0 to 0.01% by mass, calcium (Ca) in amounts of 0 to 0.01% by mass, magnesium (Mg) in amounts of 0 to 0.01% by mass, and silicon (Si) in amounts of 0 to 0.01% by mass, and contains alkali metal element ions in amounts of 0.005 to 1.2% by mass, has a basicity of 60 to 80%, and contains aluminum as Al 2 O 3 It contains 8 to 13% by mass, The hollow spherical alumina particles, as measured by laser diffraction particle size distribution measurement, have a D50 of 1.0 to 3.5 μm and a D90 of 6 μm or less, are hollow inside and spherical, and have a specific surface area of 1 to 20 m². 2 A method for producing hollow spherical alumina particles, characterized by having a density of / g.
2. The hollow spherical alumina particles have a bulk density of 0.3 to 0.7 g / cm³. 3 The method for producing hollow spherical alumina particles according to claim 1, characterized in that the crystalline phase of the hollow spherical alumina particles is the α phase.
3. The method for producing hollow spherical alumina particles according to claim 1 or 2, characterized in that the hollow spherical alumina particles exhibit a relative permittivity of 1.7 to 2.4 at a frequency f = 1 MHz measured by the capacitance method.
4. The method for producing hollow spherical alumina particles according to claim 1 or 2, characterized in that the basic aluminum lactate aqueous solution is obtained by mixing an aluminum chloride solution with either or both sodium aluminate and potassium aluminate and water to form an aluminum hydroxide gel, washing the obtained gel with water, adding water to obtain an aluminum hydroxide slurry, and then adding lactic acid and reacting it.
Citation Information
Patent Citations
Method for producing hollow spherical alumina particles
JP7560195B1